(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
Death is defined as the permanent and irreversible cessation of all biological functions that sustain life. In cases of unnatural death, such as poisoning, an inquiry is conducted by the police or magistrate under Indian law, followed by a post-mortem examination. Poisoning, particularly in suicides, is a common cause of unnatural deaths encountered during autopsies. The cause of death in such cases is confirmed only after receiving a chemical analysis report from the Forensic Science Laboratory (FSL). Viscera samples are sent for chemical analysis in suspicious death cases or when the cause of death is unclear after autopsy. Often, viscera reports return negative, making it difficult for forensic doctors to determine the exact cause of death, thereby delaying justice or, in some cases, weakening prosecution efforts. This article explores the reasons for errors in viscera reports and discusses their medico-legal implications.